If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9m+12-8m=m+12
We move all terms to the left:
9m+12-8m-(m+12)=0
We add all the numbers together, and all the variables
m-(m+12)+12=0
We get rid of parentheses
m-m-12+12=0
We add all the numbers together, and all the variables
=0
m=0/1
m=0
| 0.4x−=(0.2x+8) | | 8b=48;b=6= | | (x+3)(21)(x)=2730 | | 8(4b-20)-10b=20+12b | | 7q–11=–4 | | -17c-2+14c=-18-2c | | 9x-7+56=56 | | 4+14d=2(7d+2) | | 20x+7=5×+3 | | 5x+50=5×+3 | | 3(-5t-1)-11=3-15t | | 58.347=b-23 | | y=1,546(1+0.2)^10 | | r+3/4=17 | | -14g+20=-5g-20-7g | | -12r-12=-2(6r+6) | | -2(x+2)=2/5(5+10x | | 6x2+7x+9=0 | | -19-2n=3n+19+2 | | 1-2n+6n=-7 | | 8x+4=x+6 | | -12k-1=-6(2k-12) | | y+2/5=61/3 | | 8p-12p-13=-14-4p | | 2y+3y=135 | | Y/5y/2=15 | | -10+9m=1+14m-6m | | 3x3+-10x+9=0 | | (2x+3)+68=90 | | -8x+24-4x=-36 | | 20+13u=-20+9u-8 | | (x+2)(x)=168 |